Simple capacitance-to-time converter - Petchmaneelumka, Wandee; Wutikun, Tanatat; Rerkratn, Apinai; Riewruja, Vanchai (My University, 2017)
A method for implementing of a capacitive sensor interfacing circuit is proposed in this paper. The time period generated from a simple relaxation oscillator is utilized to determine the time period obtained from the capacitive sensor. The output parameter of the proposed converter is in the form of the time period. The capacitance of the sensor can then be calculated using ratio metric operation. The proposed converter can linearly convert the capacitance from the sensor to the time period. The purpose of the proposed converter plays an attention in terms of simple configuration and low cost. Performance of the proposed scheme is demonstrated by experimentally implementation. The resulting confirmed that the performance of the proposed converter is in good agreement with the expected value.
Keywords: Capacitance-to-time converter; Capacitive sensor; Relaxation oscillator; Resistive sensor